Erythrocyte Efferocytosis by the Arterial Wall Promotes Oxidation in Early-Stage Atheroma in Humans - Delbosc, Sandrine; Bayles, Richard Graham; Laschet, Jamila; Ollivier, Veronique; Ho-Tin-Noé, Benoit; Touat, Ziad; Deschildre, Catherine; Morvan, Marion; Louedec, Liliane; Gouya, Laurent; Guedj, Kevin; Nicoletti, Antonino; et al. (Frontiers in Cardiovascular Medicine, 2017)
Background: Since Red Blood Cells (RBCs) are the predominant cellular blood component interacting with the arterial wall we explored the role of RBCs efferocytosis by vascular smooth muscle cells (vSMCs) in the initiation of human atheroma. Methods and results: The comparison of human healthy aortas with aortic fatty streaks or fibroatheromas revealed that RBC angiophagy is implicated from the earliest stages of atherogenesis, as documented by the concomitant detection of redox-active iron, hemoglobin, glycophorin A, and ceroids. RBCs infiltration in the arterial wall was associated with local lipid and protein oxidation, as well as vascular response (expression of heme oxygenase-1 and of genes related to iron metabolism as well as those encoding for phagocytosis. These effects were recapitulated in vitro when vSMCs were co-cultured with phosphatidyl-exposing senescent (s) RBCs but not with fresh RBCs. VSMCs engulfing sRBC increased their intracellular iron content, accumulated hemoglobin, lipids, and activated their phagolysosomes. Strikingly, injections of sRBCs into rats promoted iron accumulation in the aortic wall. In rabbits, hypercholesterolemia increased circulating senescent RBCs and induced the subendothelial accumulation of iron-rich phagocytic foam cells. RBCs bring cholesterol and iron/heme into the vascular wall and interact with vSMCs that phagocytize them. Conclusions: This study presents a previously unforeseen mechanism of plaque formation that implicates intimal RBC infiltration as one of the initial triggers for foam cell formation and intimal oxidation. Pathogenic effects exerted by several metabolic and hemodynamic factors may rely on their effect on RBC biology, thereby impacting how RBCs interact with the vascular wall.